Hazard Identification and Analysis of Occupational Safety and Health Risks Using the HIRARC Method in the Production Process at PT Industri Majalaya - Apid Hardiansyah; Ahmad Fajar Sidik; Riny Yolandha Parapat (PT Ilmu Data Indonesia, 2026)
The textile industry is one of the manufacturing sectors that has a high potential for occupational safety and health (K3) hazards due to the use of high-speed machines, exposure to dust, noise, chemicals, hot temperatures, and repetitive work activities. Therefore, it is necessary to systematically identify hazards and risk assessments to prevent occupational accidents and occupational diseases. This study aims to identify potential hazards, analyze the level of risk, and determine risk control recommendations in the production process at PT Industri Majalaya using the Hazard Identification, Risk Assessment, and Risk Control (HIRE). The research was conducted through field observations, interviews with workers and K3 teams, and data collection at five main workstations, namely Blowing & Carding, Ring Spinning, Weaving, Dyeing, and Finishing. The identification results showed that there were 10 potential hazards consisting of 5 physical hazards, 2 mechanical hazards, 2 chemical hazards, and 1 ergonomic hazard. The results of the risk assessment showed that 8 hazards were in the medium category with a risk value of 6–9 and 2 hazards were in the high category with a risk value of 10, namely spindle cleaning activities without engine shutdown and noise exposure in the weaving area. No extreme category risks were found. Proposed control recommendations include installation Zero-Speed Switch, Acoustic Panel, improvement of local ventilation, periodic K3 training, and increased compliance with the use of personal protective equipment. The implementation of these recommendations is expected to increase the effectiveness of risk control and support the sustainable implementation of SMK3 at PT Industri Majalaya.